Advantages of Being Multiplex - Grosso, Michael (Journal of Scientific Exploration, 2010)
This is the study of the creative potential of mediumship. It emphasizes a neglected and under-conceptualized form of creativity in the realm of personality development. Examples include the cases of mediums Pearl Curran, Hélѐne Smith, and Matthew Manning. Artists with mediumistic propensities are stressed, such as Keats, Rimbaud, Blake, Yeats, and James Merrill. There is discussion of Myers' theory of genius and how this bears on the concept of personal transformation. Myers' theory is used to shed light on Surrealism, outsider art, and the lives of Socrates and Joan of Arc. All this is comprehended under the Keatsian rubric of "soulmaking." Keywords: mediumship–creativity–multiplicity